O lugar da mulher trans no cárcere - Santos, Kalyne Alves Andrade (2020)
This dissertation investigates the place of the fulfillment of the sentence of deprivation of liberty of trans women in the Brazilian prison system, in the perspective of the speech presented in the decisions on the transfer of trans prisoners to female prisons, issued by organs of the Judiciary between the period of 2014 and 2019. In order to fulfill the research objective, the queer theory was used as a theoretical and methodological contribution. In the first chapter, vulnerability and precariousness are characterized, in the wake of Blutterian thought. It seeks to analyze elements/systems propelling vulnerability that directly affect the life of trans people in prison. The mapping of the legal norms of international and national protection of transgender people in prison, by means of exploratory research and bibliography, has also constituted a fundamental tool to evidence the existence of a precariousness characterized by the failure of normative protection for the trans population. Under the queer perspective, the critical analysis of the decisions of the STF, STJ, TJDF and the Federal District Criminal Court on the transfer of trans women to the women's prison carried out through the Decision Analysis Methodology (MAD), has shown that the place of trans women's sentencing is an issue considered problematic by the Judiciary. Finally, it was found that trans women suffer from a precariousness produced intersectionally by power systems that subordinate and invisibilize trans people's lives.